Bias due to confounders for the exposure-competing risk relationship - Lesko, Catherine R. (Epidemiology, 2017)
BACKGROUND: Epidemiologic studies that aim to estimate a causal effect of an exposure on a particular event of interest may be complicated by the existence of competing events that preclude the occurrence of the primary event. Recently, many articles have been published in the epidemiologic literature demonstrating the need for appropriate models to accommodate competing risks when they are present. However, there has been little attention to variable selection for confounder control in competing risk analyses. METHODS: We employ simulation to demonstrate the bias in two variable selection strategies: include covariates that are associated with the exposure and 1) which change the cause-specific hazard of any of the outcomes; or 2) which change the cause-specific hazard of the specific event of interest. RESULTS: We demonstrated minimal to no bias in estimators adjusted for confounders of exposure and either the event of interest or the competing event, but bias of varying magnitude in almost all estimators adjusted only for confounders of exposure and the primary outcome. DISCUSSION: When estimating causal effects for which there are competing risks, the analysis should control for confounders of both the exposure–primary outcome effect and of the exposure–competing outcome effect.